2017
DOI: 10.4236/psych.2017.814147
|View full text |Cite
|
Sign up to set email alerts
|

Gender, BMI, and Personality as Predictors of Self-Assessed Attractiveness and Intelligence

Abstract: Over 2000 students completed three short questionnaires in which they rated their general and multiple intelligence, their attractiveness and personality using a shortened measure of the Big Five. They also provided information about their weight, height, religious and political beliefs. A series of regression was performed with self-rated intelligence and attractiveness as the criterion variable. Females scored higher on Neuroticism and Agreeableness and lower on Openness, Self-estimated IQ and attractiveness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…In this respect, sex differences in mating preferences have been the focus of many large-scale studies (e.g., Bech-Sørensen & Pollet, 2016 ; Buss, 1989 ; Eastwick & Finkel, 2008 ). Across cultures, sex differences have been reported to varied extent; however, a broadly accepted difference is that men tend to value physical characteristics such as bodily attractiveness (which is related to health and fertility; e.g., Furnham & Tsoi, 2012 ) while women are more inclined to select mates who have good earning ability (which is related to providing a better condition for future offspring; e.g., Frederick, Reynolds, & Fisher, 2013 ). Such fundamental differences in choosing a mate have been replicated across various cultures and different methodologies ( Buss & Angleitner, 1989 ; Buss, Shackelford, Kirkpatrick, & Larsen, 2001 ; Furnham, 2009 ; Li, Valentine, & Patel, 2011 ).…”
mentioning
confidence: 99%
“…In this respect, sex differences in mating preferences have been the focus of many large-scale studies (e.g., Bech-Sørensen & Pollet, 2016 ; Buss, 1989 ; Eastwick & Finkel, 2008 ). Across cultures, sex differences have been reported to varied extent; however, a broadly accepted difference is that men tend to value physical characteristics such as bodily attractiveness (which is related to health and fertility; e.g., Furnham & Tsoi, 2012 ) while women are more inclined to select mates who have good earning ability (which is related to providing a better condition for future offspring; e.g., Frederick, Reynolds, & Fisher, 2013 ). Such fundamental differences in choosing a mate have been replicated across various cultures and different methodologies ( Buss & Angleitner, 1989 ; Buss, Shackelford, Kirkpatrick, & Larsen, 2001 ; Furnham, 2009 ; Li, Valentine, & Patel, 2011 ).…”
mentioning
confidence: 99%
“…BMI and perceived attractiveness were correlated. The findings revealed that those who had a lower BMI generally thought themselves to be more physically beautiful [91]. In contrast, a different study [92] demonstrates that in contemporary society, the pressure from social stereotypes regarding physical attractiveness is nearly equal for men and women.…”
Section: Discussionmentioning
confidence: 85%
“…People tend to limit themselves to exercises that feel safe, that they are comfortable performing, and that are within their capability levels [ 33 ]. The BIG 5 personality traits—agreeableness, extroversion, conscientiousness, neuroticism, and openness—can influence exercise choices [ 34 , 35 , 36 ]. Previous studies mentioned mixed results between personality traits and sports preferences, but it is generally agreed that personality impacts behavior and experiences during leisure activities [ 37 , 38 ].…”
Section: Introductionmentioning
confidence: 99%